Multiplex PCR for Simultaneous Detection of Virulence Genes in Escherichia coli - Yu, Ke xin; Thong, Kwai Lin (Malaysian Journal of Science, 2009)
Diarrhea caused by Escherichia coli infection is major cause of public health problems in developing countries. In view of the fefisit and limitations of conventional methods of detecting the virulence determinents, a multiplex Polymerase Chain Reaction (PCR) assay was optimized and developed to provide an effective, rapid, specific diagnostic tool to simultaneously detect virulence genes such as heat-stable toxin 1 (ST 1), heat- labile toxin 1 (LT 1), heat- labile toxine 2 (LT2), verotoxin1 (VT1)m virotoxin 2 (VT2) and attachment and affacement (eaeA) in photogenic E.coli.